The Existence of Anarchic State of Affairs and the Significance of Military Capability : The Southeast Asian Region Context - หงษ์ไกรเลิศ, ขวัญสุชา (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2006)
-